KOTA PROBOLINGGO MENJELANG DAN AWAL REVOLUSI: SEJARAH, KONDISI FISIK, PENDUDUK, EKONOMI DAN SOSIAL - Sapto, Ari (Jurnal Sejarah dan Budaya, 2010)
Abstract: The revolution time can not be separated by the condition before it. Probolinggo is a small city, a port city that has agricultural and plantation support- since nineteenth century has important meaning for Dutch colonial government. As a part of Mataram Kingdom in the past time, the influences of Mataram are still so strong not only in field of town physical but also on social culture spheres. But its location is near Madura Island so many Madura people migrate easily to Probolonggo. The Madura people become majority inhabitants and there was acculturation in the cultural field between Javanese and Madura. The Javanese are still industrious in agricultural field and the Madura work on variation of occupations.